2011
DOI: 10.1161/circulationaha.110.005041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Angiographic Complete Revascularization After Drug-Eluting Stent Implantation or Coronary Artery Bypass Graft Surgery for Multivessel Coronary Artery Disease

Abstract: Background-This study sought to evaluate the clinical impact of angiographic complete revascularization (CR) after drug-eluting stent implantation or coronary artery bypass graft surgery for multivessel coronary disease. Methods and Results-A total of 1914 consecutive patients with multivessel coronary disease undergoing drug-eluting stent implantation (1400 patients) or coronary artery bypass graft surgery (514 patients) were enrolled. Angiographic CR was defined as revascularization in all diseased segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 28 publications
2
56
1
2
Order By: Relevance
“…The study population was a part of the Asan Multivessel Registry and included consecutive patients with MVD who underwent PCI with DES or CABG ( Fig. 1) (2). Patients who presented with ST-segment elevation MI and/or cardiogenic shock or for whom no clinical follow-up information was available were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study population was a part of the Asan Multivessel Registry and included consecutive patients with MVD who underwent PCI with DES or CABG ( Fig. 1) (2). Patients who presented with ST-segment elevation MI and/or cardiogenic shock or for whom no clinical follow-up information was available were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who presented with ST-segment elevation MI and/or cardiogenic shock or for whom no clinical follow-up information was available were excluded. The procedures and follow-up have been described previously (2). During the study period, DES was the default stent for PCI in patients with MVD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKG'deki büyük teknik gelişmelere rağmen, komplet revaskülarizasyonun elde edilmesi hâlen çok sık değil-dir. PKG sonrası inkomplet revaskülarizasyonun (İR) prognostik etkisi çalışmalar arasında tutarsızdır [4][5][6] . Evrensel olarak kabul edilmiş bir inkomplet revaskülarizasyon tanımlaması yoktur ve PKG sonrası rezidüel koroner darlıkların ciddiyeti, derecesi ve niteliğinin hasta sonlanımlarında farklı etkilere sahip olduğu söylenilebilir.…”
Section: In Our Study We Aimed To Detect the Relation Between Residuunclassified
“…A recent meta-analysis [15] of 9 PCI studies (7 with BMS, 1 with DES, and 1 with both) demonstrated that patients undergoing CR compared to IR had significantly lower risk of mortality (RR, 0.82; 95% CI, 0.68 to 0.99; p = 0.05). Also in a large (1400 patients) DES study [16] not included in the meta-analysis [15], patients with IR had a strong tendency toward higher risk of death than those with CR over 5 years (8.8% versus 6.2%; p = 0.057). In PCI with DES compared to CABG, more frequent IR may explain higher mortality demonstrated in our meta-analysis.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%